What Do All These Numbers Mean? Data Visualization as an Innovative Methodology to Make Program Decisions - Porter, Susan G.; Koch, Stephen P.; Henderson, Andrew (Journal of MultiDisciplinary Evaluation, 2010)
Background: There is a lack of consistent, comprehensible data collection and analysis methods for evaluating teacher preparation program’s coverage of required standards for accreditation. Of particular concern is the adequate coverage of standards and competencies that address the teaching of English learners and teachers of students from culturally and linguistically diverse backgrounds. Purpose: To graphically convey the findings of a faculty survey regarding English learner and multicultural content in teacher preparation coursework in order to inform them of inadequate coverage (and saturation) of those particular teaching standards and competencies. Setting: A small teacher preparation program in a Northern California public university that prepares elementary school teachers and special education teachers. Intervention: 10 full and part-time faculty members in a teacher preparation program that prepares elementary and special education teachers. Research Design: Congruency study, in which raw data from faculty survey responses were compared with rated program responses to teacher preparation standards by means of a relational database with graphing output capabilities. Data Collection: A survey instrument was designedandadministeredtoallfacultymembers in the program. Findings: The resulting radar maps and other graphic outputs allowed faculty to clearly see where their course content aligned with the program accreditation response and where more coverage of that particular competency was necessary. Conclusions: The use of relational databases was a highly effective method for helping one teacher preparation program to visualize their progress towards meeting standards for teacher preparation in the area of student diversity and the teaching of English learners.